The robot and the bluebird - Lucas, David, 1966- (New York : Farrar, Straus, Giroux, 2008)
A broken robot makes a home for a cold, tired bluebird trying to fly south for the winter, and eventually he carries the bird to a warmer climate while she rests in the cavity where his heart used to be.
Kirkus Review
Pub Weekly
2.2
K-3.
K-3
Keywords: Birds -- Juvenile fiction; Robots -- Juvenile fiction; Birds -- Fiction; Robots -- Fiction; Birds -- Fiction; Robots -- Fiction